Actuele Picturale Expressies. - Claus, Joos; Deblond, Alex; De Pauw, Norbert; Gele Zaal, Gent (Gent : Noordstarfonds vzw, 1984)
Bouttens, Philippe ; Castelein, Ingrid ; Coucke, Jo ; Ritzen, Barthel ; Vanbeveren, Christian ; Vandekerckhove, Hans ; Van Eetvelt, Kris ; Vos, Koen
Gele Zaal, Gent, 27 oktober - 2 december 1984
kunstcatalogus